Potensi Sektor Ekonomi di Kabupaten Tuban, Bojonegoro dan Lamongan Provinsi Jawa Timur - Eka Yunila Putri Sholikhatun Nisa; Syamsul Huda (Al-Buhuts, 2023)
This study aims to find out how to analyze the potential of each economic sector and find out the magnitude of the multiplier in Tuban, Bojonegoro and Lamongan Regencies. The approach method used is to apply a type of quantitative study with secondary data types in the form of time series data obtained from the Central Bureau of Statistics. By using analysis techniques, namely location quotient, shift share, class typology and multiplier effect. The research results obtained are that there are 6 base sectors in Tuban Regency, 2 base sectors in Bojonegoro Regency and 10 base sectors in Lamongan Regency. For sectors that drive economic growth in East Java Province, there are 2 sectors in Tuban and Bojonegoro Regencies and 5 sectors in Lamongan Regency. Sectors belonging to relatively fast economic growth in Tuban, Bojonegoro and Lamongan Regencies, there are 2 economic sectors. There are 2 sectors that provide locational advantages in Tuban Regency, 3 sectors in Bojonegoro Regency and 4 sectors in Lamongan Regency. For the results of the sector class typology in quadrant I in the Tuban Regency there are 2 sectors, 4 sectors in Bojonegoro Regency and 7 sectors in Lamongan Regency. And on the results of the analysis the value of the basis multiplier is 1.31 in Tuban Regency, 1.70 in Bojonegoro Regency and 1.21 in Lamongan Regency.